Existential concerns in psychopathology: a transdiagnostic network analysis existential concerns in psychopathology - UnYoung Chavez-Baldini; Karin J.H. Verweij; Jessy Bergamin; Judy Luigjes; Roel J.T. Mocking; Damiaan Denys; Dorien H. Nieman; Nienke C. Vulink (Cogent Mental Health, 2024)
Existential concerns, such as autonomy and identity, are often overlooked although they play an important role in psychopathology and clinical practice. The aims of this study are to investigate how existential concerns relate to psychopathological symptoms and to identify important existential concerns. This study used a cross-sectional quantitative design with a transdiagnostic sample. A mixed graphical model of 4 existential and 3 symptom domains with 4 covariates was estimated in a sample of 996 individuals with various psychiatric disorders. Symptom nodes were derived from questionnaires on psychopathological symptoms and existential nodes from questionnaires on transdiagnostic psychiatric dimensions and self-esteem. The centrality metric, expected influence, was calculated to determine nodes’ cumulative influence in the network. Existential concerns were related to worse psychopathology overall, but most strongly to depressive and anxiety symptoms. The strongest cross-domain relationship was between anxiety and recognition of psychiatric disorder. Of the existential concerns, autonomy and identity were the most central nodes in the network. Our results advocate the need to address existential concerns in clinical practice and research. Conveying individual responses to experiencing psychopathology, such as recognition of disorder, and supporting autonomy or positive identity formation may be areas for intervention.